Calcinosis cutis - Loja-Oropeza, David (2019)
Fifty four year-old woman, housewife, with hypertension and past history of right breast cancer. After a household accident, warm tumors appeared that were resistant to symptomatic treatment. Radiographic studies showed two calcified lesions, one in the lateral aspect of the left arm and other in the chest wall at the level of eighth right rib. Metabolic and immunologic studies were normal.